NEDD4‐induced degradative ubiquitination of phosphatidylinositol 4‐phosphate 5‐kinase α and its implication in breast cancer cell proliferation. Issue 9 (30th May 2018) - Tran, Mai Hoang; Seo, Eunjeong; Min, Soohong; Nguyen, Quynh‐Anh T.; Choi, Juyong; Lee, Uk‐Jin; Hong, Soon‐Sun; Kang, Hyuk; Mansukhani, Alka; Jou, Ilo; Lee, Sang Yoon
Abstract: Phosphatidylinositol 4‐phosphate 5‐kinase (PIP5K) family members generate phosphatidylinositol 4, 5‐bisphosphate (PIP2), a critical lipid regulator of diverse physiological processes. The PIP5K‐dependent PIP2 generation can also act upstream of the oncogenic phosphatidylinositol 3‐kinase (PI3K)/Akt pathway. Many studies have demonstrated various mechanisms of spatiotemporal regulation of PIP5K catalytic activity. However, there are few studies on regulation of PIP5K protein stability. Here, we examined potential regulation of PIP5Kα, a PIP5K isoform, via ubiquitin‐proteasome system, and its implication for breast cancer. Our results showed that the ubiquitin ligase NEDD4 (neural precursor cell expressed, developmentally down‐regulated gene 4) mediated ubiquitination and proteasomal degradation of PIP5Kα, consequently reducing plasma membrane PIP2 level. NEDD4 interacted with the C‐terminal region and ubiquitinated the N‐terminal lysine 88 in PIP5Kα. In addition, PIP5Kα gene disruption inhibited epidermal growth factor (EGF)‐induced Akt activation and caused significant proliferation defect in breast cancer cells. Notably, PIP5Kα K88R mutant that was resistant to NEDD4‐mediated ubiquitination and degradation showed more potentiating effects on Akt activation by EGF and cell proliferation than wild‐type PIP5Kα. Collectively, these results suggest that PIP5Kα is a novel degradative substrate of NEDD4 and that the PIP5Kα‐dependent PIP2 pool contributing to breast cancer cell proliferation through PI3K/Akt activation is negatively controlled by NEDD4.